Tacrolimus prevents murine cerebral malaria. Issue 2 (29th September 2016) - Bao, Lam Quoc; Nhi, Dang My; Huy, Nguyen Tien; Hamano, Shinjiro; Hirayama, Kenji
Summary: Tacrolimus and mycophenolate mofetil are immunosuppressants frequently used in human organ transplantation. Tacrolimus is also reported to inhibit Plasmodium falciparum growth in vitro . Here, we report that tacrolimus prevented the death from cerebral malaria of Plasmodium berghei ANKA‐infected C57BL/6J mice, but not their death from malaria due to the high parasitaemia and severe anaemia. The mycophenolate mofetil‐treated mice showed higher mortality from cerebral malaria and succumbed to malaria earlier than tacrolimus‐treated littermates. Tacrolimus attenuated the infiltration of mononuclear cells including pathogenic CD8 + T cells into the brain. It appears to prevent murine cerebral malaria through the inhibition of cerebral infiltration of CD8 + T cells. Abstract : Tacrolimus rescues Plasmodium berghei ANKA‐infected mice from cerebral malaria.